Analyzing the cancer mortality-to-incidence ratios and health expenditures in the aging population: a 20-year comparative study across high-income countries - Ramadan, Majed; AlGhamdi, Shadell; Alsiary, Rawiah (Frontiers in Aging, 2025)
BackgroundThe global burden of cancer is expected to increase by 60% over the next two decades, largely due to population aging. The study aims to examine the association between cancer mortality-to-incidence ratios (MIR) with healthcare expenditures (HE), and human development index score for individuals 70 years old or older.MethodThis is an epidemiological study using publicly available data from the Global Burden of Disease (GBD) for six over the years 1990–2019. A generalized linear model was employed to examine the association between MIR, and health expenditures and health development index score.ResultsIncluded countries showed a statistically significant negative association between MIR and both HE, and HE, indicating that higher HDI and HE are associated with decreased MIR with the highest decrease was for China, the coefficient for HDI is −1.29 (95% CI: –1.35 to −1.24, p < 0.0001), the coefficient for HE is −0.103 (95% CI: –0.17 to −0.03, p < 0.0001). There are variations exist in MIRs between high and low health expenditure countries for each cancer type.ConclusionThe study reveals a significant impact of HE and HDI on cancer outcomes in older adults. Variations between high and low HE nations highlight potentially improved cancer outcomes in high HE countries. Considering the anticipated growth in the aging population worldwide, a rise in cancer cases is expected among older individuals. The implications are profound, suggesting an impending strain on healthcare systems, particularly in nations with a high proportion of elderly and low health expenditures.